ANALISIS INFLASI DAN INDEKS HARGA SAHAM KOMPOSIT TERHADAP INTEREST RATE BANK INDONESIA - Rakhmawati, Desty; Setyaningrum, Nur Anisa; Fajarwati, Septi (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The BI Interest Rate is a reference interest rate that has been set by BI, where the value of this exchange rate changes every day and has crucial functions, including controlling inflation and maintaining the stability and growth of the country's economy. Then what about inflation itself which functions to maintain economic stability. The financial stability of a nation can also be seen from the composite stock price index. Then do inflation and the Composite Stock Price Index (IHSG) also have an influence on the interest rate. Thus, this research aims to analyze the impact of inflation and IHSG on the BI interest rate, which is an important thing in the country's economy. Influence analysis was carried out using monthly time series data from January 2019 to December 2023. This data is inflation data (X1), IHSG data (X2), and interest rate data (Y). Data analysis was carried out by creating a linear regression model and carrying out classical assumption tests. After carrying out all tests and fulfilling the requirements for classical assumption testing at a significance level of 5%, the result was that inflation data had an effect on BI interest rates, whereas in this study it showed that the IHSG was not significant